Efficient Caching of Data Using Fast Wireless Data Access Scheme - Buddesab, Buddesab; Kashyap, Santhosh S; Hugge, Channabasappa (International Journal of Computer Sciences and Engineering, 2025)
In Wireless Data Access Applications where objects are frequently updated and fast access to objects is required and it is essential to reduce both access latency and the wireless traffic. So in this project we propose FW-DAS (Fast Wireless Data Access Scheme). This extends Poll-Every-Read and Call Back Scheme in Combination. Fast Wireless Data access Scheme (FWDAS) is used to improve performance by caching the data at user level and server level. Caching of data is done based on data popularity. In FWDAS three data models are defined and used based on data popularity of the data object. FWDAS uses different operations on the data based on data popularity of the data object. Only popular object are proactively pushed to the servers thus reducing the access latency while mitigating the traffic load over the network